Hibridismo organizacional e desenvolvimento de competências empreendedoras para legitimação de negócios de impacto - Schmittel, Richardson Moro (2023)
Acquiring skills to undertake impact businesses can be a challenge, since balancing economic and social missions can bring conflicting objectives due to the organizational hybridity of these businesses. The thesis analyzed in-depth interviews with entrepreneurs, websites, networks and documents to understand how impact business entrepreneurs interpret their context of action and develop skills to seek legitimacy for their impact venture in an ecosystem immersed in a conflict of institutional logics. The analysis was carried out from the perspective of critical realism and it was identified that the entrepreneur recognizes the importance of economic logic within the ecosystem and the importance of obtaining money and financing, but always valuing altruism and collaboration. Within this context, the entrepreneur seeks to develop his skills through an interactive and recursive process, in which he is influenced and seeks to influence the structures and actors of the ecosystem.